2013
DOI: 10.1016/j.soncn.2013.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Navigation as an Intervention to Eliminate Disparities in American Indian Communities

Abstract: Objective To identify the role of patient navigation in decreasing healthcare disparities through an exemplar of a successful patient navigation program for American Indian populations living in the Northern and Southern Plains of the US. Data Sources Published literature and data from the Native Navigators and the Cancer Continuum study. Conclusion Native Patient Navigators successfully collaborated with local American Indian organizations to provide cancer education through a series of 24-hour workshops.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 23 publications
2
38
0
Order By: Relevance
“…However, in describing their experiences with the program, the predominant recurring theme was the depth of emotional support the navigator provided, in particular for those who did not have strong personal support systems in place. Other studies have identified similar categories of navigator tasks as valued by patients, although participants of this study were less likely to mention financial assistance, help with insurance benefits, and child/elder care (Braun et al, 2012; Burhansstipanov et al, 1998; Carroll et al, 2010; Domingo, Davis, Allison, & Braun, 2011; Gabitova & Burke, 2014; Krebs et al, 2013; Petereit et al, 2008). …”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, in describing their experiences with the program, the predominant recurring theme was the depth of emotional support the navigator provided, in particular for those who did not have strong personal support systems in place. Other studies have identified similar categories of navigator tasks as valued by patients, although participants of this study were less likely to mention financial assistance, help with insurance benefits, and child/elder care (Braun et al, 2012; Burhansstipanov et al, 1998; Carroll et al, 2010; Domingo, Davis, Allison, & Braun, 2011; Gabitova & Burke, 2014; Krebs et al, 2013; Petereit et al, 2008). …”
Section: Discussionmentioning
confidence: 67%
“…Other patient navigator programs also reported uncertainty about the navigator’s role within the health care team as a weakness (Gabitova & Burke, 2014), a finding that was congruent with our results. However, as cancer patient navigation moves towards professional certification, researchers are making progress toward defining the navigator’s role and developing core competencies, including those programs specifically aimed at serving indigenous populations (Braun et al, 2012; Burhansstipanov et al, 1998; Carroll et al, 2010; Domingo et al, 2011; Gabitova & Burke, 2014; Krebs et al, 2013; Petereit et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Undocumented individuals, who have been in the US for several years, are more cautious in sharing information whereas new arrivals are less cautious. The lack of trust in the medical system by many American Indians/Alaska Natives and resistance to taking part in research studies is well documented (6, 6567). In Appalachian communities, there is a general distrust of outsiders.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that cancer education modules are able to increase cancer knowledge and cancer-screening behaviors in this community. 27 A head and neck cancer module with information about HPV should be developed. Targeted screenings of tobacco users should be undertaken in an effort to provide early access to diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%